Development of an older adult Nutrition Equity Index (NEI) and association with the Healthy Eating Index (HEI) in older Black and White U.S. adults - Aarohee P. Fulay; Samaneh Farsijani; Kerri Freeland; Jimmie Roberts; Andrea L. Rosso; Denise K. Houston; Elsa S. Strotmeyer (The Journal of Nutrition, Health and Aging)
Objectives: We developed a novel measure for older U.S. adults called the Nutrition Equity Index (NEI), which includes functional ability. We compared both the NEI and food insufficiency with Healthy Eating Index (HEI) scores. Design: The Health, Aging, and Body Composition Study is a prospective, longitudinal cohort of Medicare-eligible, community-dwelling Black and White men and women. Setting: Pittsburgh, PA and Memphis, TN. Participants: Participants (N = 2468, aged 74.7 ± 2.9 years) had baseline (1997−98) and 1-year follow-up NEI data; and 1 year follow-up for food insufficiency, key covariates, and the HEI (diet quality measure) from a 108-item interviewer-administered food frequency questionnaire. Measurements: Food insufficiency was defined from a modified validated question on ample food amount/variety from the U.S. Department of Agriculture. NEI was constructed from 8 questions in three subdomains: food insecurity (food insufficiency, hunger, anxiety about limited food, limited money for food), food access (groceries), and food acquisition (difficulty shopping, preparing meals, carrying groceries). Final NEI categories were low nutrition equity (0), moderate nutrition equity (1), and high nutrition equity (2). Multivariable linear regression compared both NEI and food insufficiency with HEI, adjusted for sociodemographic, lifestyle and comorbidity factors. Results: Of participants, 13.5% had food insufficiency, 12.1% had low NEI, and 32.5% had moderate NEI. Participants with food insufficiency (vs. food sufficiency) or low NEI (vs. high NEI) were more likely to be Black and have < high school education (both p < 0.0001). In minimally adjusted models, food insufficiency was associated with 2.2 point lower HEI score (p = 0.001), low NEI with 2.6 point lower HEI score (p = 0.001), and moderate NEI with 1.0 point lower HEI score (p < 0.05). Adjusting for race attenuated NEI associations with HEI to non-significance. After multivariable adjustment, food insufficiency was associated with 1.5 point lower HEI score (p = 0.03). Conclusion: Food insufficiency was associated with lower dietary quality in this sample of older Black and White U.S. adults. NEI performed similarly to food insufficiency for HEI associations prior to multivariable adjustment and identified more older adults with nutrition inequity, who may be at risk for poor health outcomes.